Seorang Laki-Laki Usia 27 Tahun dengan Gangguan Panik - Kadek Aryati; Cahyaningsih Fibri R (Medula, 2020)
Panic disorder is an ongoing public health problem. Panic disorder is an unexpected experience of panic attacks followed by persistent fears about the possibility of repeated attacks or changes in behavior in daily life as a result of these attacks. Women 2-3 times more suffer from this disorder than men. there are very anxiety episodes, their duration is short, repetitive, and unpredictable, followed by typical clinical manifestations. Factors that influence biological, genetic or psychosocial factors. Management with pharmacotherapy and psychotherapy. In this case, a 27-year-old man with complaints of fear and anxiety that occurred suddenly and did not know the cause since 6 months ago. Feelings of fear and anxiety come at any time and in any situation.